Silicate system electrolyte and surface micro-arc oxidation method of locally encapsulated magnesium alloy

After locally encapsulating the magnesium alloy, the silicate system electrolyte is used to increase the concentration of fluorinated salt and phosphate, and the problem of melting or burning of plastic in the microarc oxidation process of magnesium alloy is solved, achieving a more dense Coating and lower processing time.

CN119465341APending Publication Date: 2025-02-18SHANGHAI KINDOE NEW MATERIALS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411559238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the magnesium alloy is partially coated and undergoes microarc oxidation treatment, the glue-covered plastic often melts or burns the glue, resulting in product damage.

Method used

The silicate system electrolyte is used to increase the concentration of fluoride salt and introduce phosphate or phytic acid as a sintering inhibitor to adjust the pH value and arc parameters of the electrolyte to reduce the terminal voltage of microarc oxidation and coating roughness.

Benefits of technology

It effectively reduces the intensity of the microarc oxidation process, avoids the glue burning phenomenon at the glue-encapsulated area, improves the density of the microarc oxidation coating and its binding force with the matrix, and shortens the processing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465341A_ABST
    Figure CN119465341A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy surface treatment, and provides silicate system electrolyte and a partially encapsulated magnesium alloy surface micro-arc oxidation method, the silicate system electrolyte comprises silicate with the concentration of 15-25 g / L, an ablation inhibitor with the concentration of 10-15 g / L, a pH regulator with the concentration of 2-8 g / L and a glue burning inhibitor with the concentration of 5-15 g / L, and deionized water serves as a solvent; wherein the ablation inhibitor is fluoride salt, and the glue burning inhibitor is phosphate or phytic acid. According to the invention, fluoride salt as an ablation inhibitor and phosphate or phytic acid as a glue burning inhibitor are jointly added into a silicate system, and respective concentrations of the fluoride salt and the phosphate or phytic acid are strictly controlled, so that the technical problem of ablation or glue burning of the plastic locally encapsulated with the magnesium alloy is jointly solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy surface treatment, and in particular relates to a silicate system electrolyte and a micro-arc oxidation method for the surface of a partially encapsulated magnesium alloy. Background Art

[0002] The trend of thinness and lightness of 3C products has been sought after by consumers, while the shells of traditional 3C products are mostly made of plastic. Although they are light in weight, their ability to prevent electromagnetic interference is not as good as that of metal materials. The unique characteristics of magnesium alloys, such as lightness, beauty, electromagnetic shielding performance, good heat dissipation, excellent specific strength and specific stiffness, and good feel, have led to a rapid rise in the application of 3C products. At present, many shells of mobile phones, laptops, cameras, etc. produced by companies such as Huawei, Apple, and Sony use magnesium alloys. AZ91 material has higher strength, impact resistance, dent resistance, and easy processing properties than conventional magnesium alloys and is widely used in the 3C industry. However, AZ91 magnesium alloy still has the characteristics of high chemical activity of magnesium alloys. It is very easy to be corroded when directly exposed to the atmospheric environment. Anti-corrosion treatment is still an important research direction.

[0003] Magnesium alloy surface treatment technology is an effective way to expand its use scenarios and extend its service life. Therefore, reliable surface treatment technology has become the key to breaking the use of magnesium alloys. The common properties of micro-arc oxidation coatings are strong designability, high coating hardness and good wear resistance. In recent years, micro-arc oxidation technology has gradually been applied to the corrosion protection of magnesium alloys. After continuous improvement by researchers, the application of micro-arc oxidation in the corrosion protection of magnesium alloys has become more and more extensive. Magnesium alloy micro-arc oxidation coatings can improve the corrosion resistance and surface hardness of magnesium alloys. In the micro-arc oxidation of magnesium alloys, the coating hardness can reach 500-1000HV.

[0004] Although micro-arc oxidation technology has been widely used to improve the corrosion resistance of magnesium alloys, when some new demands emerge, such as magnesium alloys that need to be partially coated and then micro-arc oxidized, the plastic coating often melts or even burns, resulting in product damage. Therefore, it has become an urgent problem to perform micro-arc oxidation on AZ91 partially coated products without affecting the appearance of the coated part. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a silicate system electrolyte and a method for micro-arc oxidation of the surface of a partially encapsulated magnesium alloy. The present invention reduces the terminal voltage of the magnesium alloy by about 20V during micro-arc oxidation, while reducing the roughness of the micro-arc oxidation coating and the time of micro-arc oxidation, thereby reducing the severity of micro-arc oxidation during arc discharge from several aspects.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A silicate system electrolyte, comprising silicate at a concentration of 15-25 g / L, an ablation inhibitor at a concentration of 11-15 g / L, a pH regulator at a concentration of 2-8 g / L, a burn inhibitor at a concentration of 5-15 g / L, and a solvent of deionized water;

[0008] Wherein, the ablation inhibitor is a fluoride salt, and the burnout inhibitor is a phosphate or phytic acid.

[0009] The silicate may be sodium silicate or potassium silicate.

[0010] Preferably, the fluoride salt is sodium fluoride or potassium fluoride.

[0011] Preferably, the phosphate is selected from potassium phosphate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium hexametaphosphate, potassium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or disodium glycerophosphate.

[0012] Preferably, the pH value of the silicate system electrolyte is 12-13.5.

[0013] Preferably, the pH adjuster is sodium hydroxide or potassium hydroxide.

[0014] Based on the same inventive concept, the present invention also provides a method for micro-arc oxidation of the surface of a partially encapsulated magnesium alloy using the above-mentioned electrolyte, comprising the following steps:

[0015] S1: prepare electrolyte;

[0016] S2: cleaning the surface of the magnesium alloy;

[0017] S3: placing the magnesium alloy treated in step S2 in the electrolyte for micro-arc oxidation to obtain a micro-arc oxidation coating on the surface of the magnesium alloy.

[0018] Preferably, in step S3, micro-arc oxidation is performed using a magnesium alloy as an anode and a stainless steel plate as a cathode.

[0019] Preferably, during the micro-arc oxidation process in step S3, a constant current control method is adopted, and the current density is 0.5-5A / dm 2 , the frequency range is 400-2000Hz, the duty cycle is 5-35%, and the time is 10-50min.

[0020] Preferably, the thickness of the micro-arc oxidation coating is 10-50 μm.

[0021] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:

[0022] The present invention increases the ablation inhibitor content of fluoride salt in the silicate system, which can reduce the intensity of the arc discharge process, make the generated arc more dense, the local arc energy is lower, and the generated heat is more dispersed, so that the heat is more easily taken away by the potion, thereby avoiding the accumulation of heat and causing the ablation of the plastic at the encapsulation. The phenomenon manifested in the product is that the surface of the micro-arc oxidation coating is denser and the roughness is lower; at the same time, the introduction of phosphate or phytic acid can increase the micro-arc oxidation film forming speed, reduce the porosity of the oxide film, improve its density, enhance the bonding force with the substrate, and change the composition of the oxide film, while reducing the termination voltage of the micro-arc oxidation. The high or low termination voltage reflects the intensity of the micro-plasma chemical reaction on the substrate surface. Increasing the film forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of the arc discharge. By reducing the voltage of the micro-arc oxidation, the intensity of the reaction is reduced. The excess heat generated by the micro-arc oxidation process can be quickly cooled by the potion, avoiding the accumulation of heat on the plastic and causing the phenomenon of burning of the encapsulated part.

[0023] When the concentration of the ablation inhibitor is less than 10 g / L or the concentration of the burn-out inhibitor is less than 5 g / L, the above-mentioned effect cannot be achieved. When the concentration of the ablation inhibitor is greater than 15, the film formation speed will be accelerated too quickly, which will bring unreliable side effects. Therefore, the concentration of the burn-out inhibitor of the present invention is 5-15 g / L. For cost considerations, the concentration of the ablation inhibitor is 10-15 g / L.

[0024] Therefore, the present invention adds fluoride salt and phosphate or phytic acid additives to the silicate system to solve the technical problem of ablation or burning of plastic partially encapsulating magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The change of terminal voltage during micro-arc oxidation in Example 1 of the present invention and Comparative Example 6;

[0026] Figure 2 The changes in film thickness and time of the micro-arc oxidation coating of Example 4 of the present invention and Comparative Example 6;

[0027] Figure 3 The roughness comparison of the micro-arc oxidation coating of Example 1 of the present invention and Comparative Example 6;

[0028] Figure 4 This is the appearance of the encapsulation after micro-arc oxidation in Example 1 of the present invention;

[0029] Figure 5 This is the appearance of the encapsulation after micro-arc oxidation in Example 2 of the present invention;

[0030] Figure 6 This is the appearance of the encapsulation after micro-arc oxidation in Example 3 of the present invention;

[0031] Figure 7 This is the appearance of the encapsulation after micro-arc oxidation in Example 4 of the present invention;

[0032] Figure 8 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 1 of the present invention;

[0033] Fig. 9 This is the appearance of the encapsulation after micro-arc oxidation in Comparative Example 2 of the present invention;

[0034] Fig.10 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 3 of the present invention;

[0035] Fig.11 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 4 of the present invention;

[0036] Fig.12 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 5 of the present invention;

[0037] Fig.13 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0038] It should be noted that in products such as mobile phones and notebooks, due to the consideration of signals and other factors in the magnesium alloy skeleton or specific positions of the panel, the magnesium alloy products need to be partially encapsulated, and then the products are subjected to overall micro-arc oxidation treatment, and the appearance of the encapsulated area must not be affected. However, the AZ91 magnesium alloy reacts violently in the traditional alkaline silicate system. During the arc discharge stage, the sparks generated by the arc are coarse and bright, resulting in a high local instantaneous temperature on the surface of the magnesium alloy in the electrolyte. Micro-arc oxidation also relies on the instantaneous high temperature generated during the arc discharge process to melt and cool the oxide to form a micro-arc oxidation coating. In this process, the higher the voltage, the more violent the reaction, the higher the local instantaneous temperature, and the higher the roughness of the generated micro-arc oxidation coating.

[0039] The current problem of magnesium alloy and local encapsulation process burning glue during micro-arc oxidation is mainly due to the alkaline silicate solution system used in common micro-arc oxidation. The arc discharge stage of micro-arc oxidation reacts violently, and the arc spark is coarse and strong. At this time, the local instantaneous temperature is high, and the heat generated on the surface of the magnesium alloy cannot be quickly cooled by the solution, causing the temperature of the plastic at the junction of the magnesium alloy and the plastic to rise. As the reaction continues, the heat gradually accumulates, eventually causing the plastic to burn. In addition, during micro-arc oxidation, the higher the voltage, the more violent the reaction, and the risk of burning at the encapsulation will also increase.

[0040] Therefore, in view of the above reasons, the present invention adopts the method of increasing the fluoride salt content in the alkaline silicate system and introducing a phosphate additive to jointly solve the problem of glue burning at the encapsulation site.

[0041] The concentration of the fluoride salt of the present invention is greater than 10g / L, which increases the sodium fluoride content, can reduce the intensity of the arc discharge process, make the generated arc more dense, the local arc energy is lower, and the generated heat is more dispersed, so that the heat is more easily taken away by the potion, thereby avoiding the accumulation of heat and causing the ablation of the plastic at the encapsulation. The phenomenon manifested in the product is that the surface of the micro-arc oxidation coating is denser and the roughness is lower. The introduction of phosphate or phytic acid can increase the micro-arc oxidation film-forming speed, reduce the porosity of the oxide film, improve its density, enhance the bonding force with the substrate, and change the composition of the oxide film, while reducing the termination voltage of the micro-arc oxidation. The high or low termination voltage reflects the intensity of the micro-plasma chemical reaction on the surface of the substrate; increasing the film-forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of the arc discharge. By reducing the voltage of the micro-arc oxidation, the intensity of the reaction is reduced; the excess heat generated by the micro-arc oxidation process can be quickly cooled by the potion, avoiding the accumulation of heat on the plastic and causing the phenomenon of burning of the encapsulated part.

[0042] The following is a further detailed description of a silicate system electrolyte and a method for micro-arc oxidation of a partially coated magnesium alloy surface proposed by the present invention in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description.

[0043] Example 1

[0044] 1. Preparation of electrolyte

[0045] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, phytic acid.

[0046] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and phytic acid and add them to pure water, stir them thoroughly to dissolve, and prepare solutions A / B / C / D, and then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and phytic acid are 20g / L, 15g / L, 4g / L, and 10g / L, respectively, and the solution pH is 12.5-13.0.

[0047] 2. Electrolytic oxidation film formation

[0048] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The entire process is produced in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , the temperature is 20-30℃, and the time is 30min. After the micro-arc oxidation is completed, the product is washed and dried, and the thickness of the obtained micro-arc oxidation coating is 28-30μm. Figure 4 As shown, there is no burning of the rubber part.

[0049] Example 2

[0050] 1. Preparation of electrolyte

[0051] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0052] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, and then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and phytic acid are 22g / L, 12g / L, 4g / L, and 7g / L, respectively, and the solution pH is 13.0-13.2.

[0053] 2. Electrolytic oxidation film formation

[0054] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The entire process is produced in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , the temperature is 20-30℃, and the time is 30min. After the micro-arc oxidation is completed, the product is washed and dried, and the thickness of the obtained micro-arc oxidation coating is 28-30μm. Figure 5 As shown, there is no burning of the rubber part.

[0055] Example 3

[0056] 1. Preparation of electrolyte

[0057] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0058] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate are 22g / L, 11g / L, 4g / L, and 5g / L, respectively, and the solution pH is 12.8-13.0.

[0059] 2. Electrolytic oxidation film formation

[0060] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2, temperature is 20-30℃, time is 35min. After the micro-arc oxidation is completed, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm. After the phosphate concentration is reduced, the micro-arc oxidation time will increase, and there will be no burning of the rubber part (such as Figure 6 shown).

[0061] Example 4

[0062] 1. Preparation of electrolyte

[0063] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0064] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate are 22g / L, 11g / L, 4g / L, and 15g / L, respectively, and the solution pH is 13.2-13.5.

[0065] 2. Electrolytic oxidation film formation

[0066] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 25min. After the micro-arc oxidation, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm. As the phosphate concentration increases, the micro-arc oxidation time will decrease, but the surface roughness of the film layer will increase, indicating that the reaction is proceeding in a more intense direction, and there is no burning of the rubber part (such as Figure 7 shown).

[0067] Comparative Example 1

[0068] 1. Preparation of electrolyte

[0069] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0070] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, and then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate are 22g / L, 12g / L, 4g / L, and 17g / L, respectively, and the solution pH is 13.2-13.5.

[0071] 2. Electrolytic oxidation film formation

[0072] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 23min. After the micro-arc oxidation, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm. As the phosphate concentration increases, the micro-arc oxidation time is further reduced, and the surface roughness of the film layer increases, indicating that the reaction is proceeding in a more intense direction. At this time, a slight burning phenomenon occurs in the encapsulated part (such as Figure 8 shown).

[0073] Comparative Example 2

[0074] 1. Preparation of electrolyte

[0075] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0076] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, and then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate are 22g / L, 12g / L, 4g / L, and 4g / L, respectively, and the solution pH is 13.2-13.5.

[0077] 2. Electrolytic oxidation film formation

[0078] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 35min. After the micro-arc oxidation is completed, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm. As the phosphate concentration decreases, the micro-arc oxidation time is prolonged, and a slight burning phenomenon occurs (such as Fig. 9 shown).

[0079] Comparative Example 3

[0080] 1. Preparation of electrolyte

[0081] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate.

[0082] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate and add them to pure water, fully dissolve them, and prepare solutions A / B / C / D, and then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, sodium hydroxide, and sodium hexametaphosphate are 22g / L, 8g / L, 4g / L, and 12g / L, respectively, and the solution pH is 13.2-13.5.

[0083] 2. Electrolytic oxidation film formation

[0084] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 30min. After the micro-arc oxidation is completed, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm. As the phosphate concentration decreases, the micro-arc oxidation time is prolonged, and a slight burning phenomenon occurs (such as Fig.10 shown).

[0085] Comparative Example 4

[0086] 1. Preparation of electrolyte

[0087] Raw materials: sodium silicate, sodium hydroxide, sodium hexametaphosphate.

[0088] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium hydroxide, and sodium hexametaphosphate and add them into pure water, fully dissolve them, and prepare solutions A / C / D, then mix and dilute the four solutions. The concentrations of sodium silicate, sodium hydroxide, and sodium hexametaphosphate are 20g / L, 4g / L, and 15g / L, respectively, and the solution pH is 13.2-13.5.

[0089] 2. Electrolytic oxidation film formation

[0090] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 30min. After the micro-arc oxidation is completed, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm, and the rubber-coated part has a burning phenomenon (such as Fig.11 shown).

[0091] Comparative Example 5

[0092] 1. Preparation of electrolyte

[0093] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide.

[0094] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, and sodium hydroxide and add them to pure water, fully dissolve them, and prepare solutions A / B / C, then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, and sodium hydroxide are 20g / L, 12g / L, and 4g / L, respectively, and the solution pH is 13.0-13.2.

[0095] 2. Electrolytic oxidation film formation

[0096] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 35min. After the micro-arc oxidation, the product is washed and dried. The thickness of the micro-arc oxidation film is 28-30μm, and the rubber part is ablated (such as Fig.12 shown).

[0097] Comparative Example 6

[0098] 1. Preparation of electrolyte

[0099] Raw materials: sodium silicate, sodium fluoride, sodium hydroxide.

[0100] Electrolyte preparation process: Take a certain amount of sodium silicate, sodium fluoride, and sodium hydroxide and add them to pure water, fully dissolve them, and prepare solutions A / B / C, then mix and dilute the four solutions. The concentrations of sodium silicate, sodium fluoride, and sodium hydroxide are 18g / L, 6g / L, and 4g / L, respectively, and the solution pH is 13.0-13.2.

[0101] 2. Electrolytic oxidation film formation

[0102] Preparation process: A single pulse micro-arc oxidation power supply is used to micro-arc oxidation the encapsulated AZ91 magnesium alloy product. The AZ91 magnesium alloy product to be treated is placed at the anode of the micro-arc oxidation power supply, and the cathode is a stainless steel plate. The whole process is carried out in a constant current mode with a frequency of 1500Hz, a duty cycle of 30%, and a current density of 2A / dm 2 , temperature is 20-30℃, time is 30min. After the micro-arc oxidation, the product is washed and dried. The thickness of the micro-arc oxidation film is 23-25μm. The encapsulated part is severely ablated (such as Fig.13 shown).

[0103] The electrolyte, time, and coating thickness obtained in the micro-arc oxidation process of the embodiments and comparative examples are summarized in the following table:

[0104]

[0105] Figure 1 The voltage changes during micro-arc oxidation of Example 1 and Comparative Example 6 are shown. It can be seen from the figure that the voltage of Example 1 is lower than that of Comparative Example 6. Figure 3 From the roughness comparison, it can be seen that the roughness of the micro-arc oxidation coating of Example 1 is smaller than that of the micro-arc oxidation coating of Comparative Example 6. It can be seen that increasing the concentration of sodium fluoride and introducing a burnout inhibitor can reduce the voltage during micro-arc oxidation and reduce the intensity of micro-arc oxidation during arc discharge. At the same time, it reduces the roughness of the micro-arc oxidation coating and avoids the phenomenon of plastic burnout. Figure 2 From the graph of the change in film thickness and time of the micro-arc oxidation coating of Example 4 and Comparative Example 6, it can be seen that the film forming speed of Example 4 is greater than the film forming speed of Comparative Example 6. The increase in film forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of arc discharge.

[0106] Compare the appearance of the encapsulated area after micro-arc oxidation of the embodiment with that of comparative examples 1-6, see Figure 4-13 It can be seen that only when the concentration of sodium fluoride is increased and the ablation inhibitor is introduced at the same time, and the concentration of sodium fluoride is greater than 8g / L, and the concentration of the ablative agent is 5-15g / L, can the rubber-coated part after micro-arc oxidation be prevented from burning.

[0107] Therefore, the present invention increases the sodium fluoride concentration to 10g / L and introduces phosphate or phytic acid into the silicate system, and the phosphate or phytic acid concentration is within the range of 5-15g / L, so that the terminal voltage of the magnesium alloy is reduced by about 20V during micro-arc oxidation, and the roughness of the micro-arc oxidation coating is reduced, and the time of micro-arc oxidation is reduced. From these aspects, the intensity of micro-arc oxidation during arc discharge is reduced, thereby avoiding the phenomenon of plastic burning.

[0108] For some magnesium alloy products having a large number of sharp edges and sharp angles after mechanical processing, the present invention reduces the severity of the micro-arc oxidation reaction and can reduce the risk of sharp edge and sharp angle ablation caused by tip discharge to a certain extent.

[0109] The electrolyte provided by the present invention can be used not only on magnesium alloy products with rubber coating, but also on magnesium alloy products without rubber coating. Reducing voltage and shortening film growth time can save energy consumption of products and increase production efficiency. In addition, the roughness of the micro-arc oxidation coating of the present invention is significantly reduced compared with the traditional silicate system, and is also applicable to some magnesium alloy products that require surface roughness.

[0110] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.

Claims

1. A silicate system electrolyte, characterized in that: The silicate system electrolyte comprises silicate at a concentration of 15-25 g / L, ablation inhibitor at a concentration of 11-15 g / L, pH regulator at a concentration of 2-8 g / L, and a sintering inhibitor at a concentration of 5-15 g / L, and the solvent is deionized water; Wherein, the ablation inhibitor is a fluoride salt, and the burnout inhibitor is a phosphate or phytic acid.

2. The silicate system electrolyte according to claim 1, characterized in that: The fluoride salt is sodium fluoride or potassium fluoride.

3. The silicate system electrolyte according to claim 1, characterized in that: The phosphate is selected from potassium phosphate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium hexametaphosphate, potassium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or disodium glycerophosphate.

4. The silicate system electrolyte according to claim 1, characterized in that: The pH value of the silicate system electrolyte is 12-13.

5.

5. The silicate system electrolyte according to claim 1 or 4, characterized in that: The pH adjuster is sodium hydroxide or potassium hydroxide.

6. A method for micro-arc oxidation on the surface of a partially coated magnesium alloy using the electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: prepare electrolyte; S2: cleaning the surface of the magnesium alloy; S3: placing the magnesium alloy treated in step S2 in the electrolyte for micro-arc oxidation to obtain a micro-arc oxidation coating on the surface of the magnesium alloy.

7. The method for micro-arc oxidation of a partially coated magnesium alloy surface by an electrolyte according to claim 6, characterized in that: In step S3, micro-arc oxidation is performed using the magnesium alloy as the anode and the stainless steel plate as the cathode.

8. The method for micro-arc oxidation of a partially coated magnesium alloy surface by an electrolyte according to claim 6, characterized in that: During the micro-arc oxidation process in step S3, a constant current control method is adopted, and the current density is 0.5-5A / dm 2 , the frequency range is 400-2000Hz, the duty cycle is 5-35%, and the time is 10-50min.

9. The method for micro-arc oxidation of a partially coated magnesium alloy surface by an electrolyte according to claim 8, characterized in that: The thickness of the micro-arc oxidation coating is 10-50 μm.